2019
DOI: 10.1074/jbc.ra118.007213
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatic heparan sulfate is a master regulator of hepcidin expression and iron homeostasis in human hepatocytes and mice

Abstract: Hepcidin is a liver-derived peptide hormone that controls systemic iron homeostasis. Its expression is regulated by the bone morphogenetic protein 6 (BMP6)/SMAD1/5/8 pathway and by the proinflammatory cytokine interleukin 6 (IL6). Proteoglycans that function as receptors of these signaling proteins in the liver are commonly decorated by heparan sulfate, but the potential role of hepatic heparan sulfate in hepcidin expression and iron homeostasis is unclear. Here, we show that modulation of hepatic heparan sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Differential gene expression analysis revealed that 80/85, 95/89 and 261/902 genes were significantly [abs(logFC) ≥ 1.5 and FDR ≤ 0.05] up/downregulated after 2, 6 and 12 months of CCl 4 treatment compared to olive oil controls, respectively, with partially very strong, more than 1000-fold expression changes ( Figure 2C; lists of differential genes: Table S1). Strongly and consistently upregulated genes ( Figure 2D) comprise extracellular matrix-associated genes, such as Col28a1, whose role in liver fibrosis is well-known; the variable domains of immunoglobulin heavy chains, suggesting infiltration of B cells/plasma cells [37], e.g., Ighv10-3, Ighv1-9, Ighv4-57-1, Ighv1-22, Ighv4-57-1; the liver-derived peptide hormone hepcidin-2 which supports iron homeostasis [38]; and some factors that so far have not been considered as primary genes affected by liver damage, such as gliomedin (Gldn), a protein expressed by myelinating Schwann cells [39] and the leucine-rich repeat and transmembrane domain-containing protein 2 (Lrtm2). Among the strongest downregulated genes ( Figure 2D) are several major urinary proteins (Mups), also known as α 2 µ-globulins, such as Mup19, Mup21, Mup15, Mup17, Mup-ps16, Mup-ps14 and Mup12.…”
Section: Rna-seq Demonstrates Downregulation Of Pericentral and Upregmentioning
confidence: 99%
“…Differential gene expression analysis revealed that 80/85, 95/89 and 261/902 genes were significantly [abs(logFC) ≥ 1.5 and FDR ≤ 0.05] up/downregulated after 2, 6 and 12 months of CCl 4 treatment compared to olive oil controls, respectively, with partially very strong, more than 1000-fold expression changes ( Figure 2C; lists of differential genes: Table S1). Strongly and consistently upregulated genes ( Figure 2D) comprise extracellular matrix-associated genes, such as Col28a1, whose role in liver fibrosis is well-known; the variable domains of immunoglobulin heavy chains, suggesting infiltration of B cells/plasma cells [37], e.g., Ighv10-3, Ighv1-9, Ighv4-57-1, Ighv1-22, Ighv4-57-1; the liver-derived peptide hormone hepcidin-2 which supports iron homeostasis [38]; and some factors that so far have not been considered as primary genes affected by liver damage, such as gliomedin (Gldn), a protein expressed by myelinating Schwann cells [39] and the leucine-rich repeat and transmembrane domain-containing protein 2 (Lrtm2). Among the strongest downregulated genes ( Figure 2D) are several major urinary proteins (Mups), also known as α 2 µ-globulins, such as Mup19, Mup21, Mup15, Mup17, Mup-ps16, Mup-ps14 and Mup12.…”
Section: Rna-seq Demonstrates Downregulation Of Pericentral and Upregmentioning
confidence: 99%
“…A general understanding of this regulatory network is that inflammation brought about by infections increases hepcidin production, which in turn can lead to the anemia of inflammation [ 50 , 52 ]. Hepcidin production in the liver is induced by IL-6 [ 51 , 94 ], and it has been reported that hepatic heparan sulfate affects and regulates IL-6-stimulated hepcidin expression [ 103 ]. Furthermore, heparin, the anticoagulant glycosaminoglycan that is a highly sulfated form of heparan sulfate, has been shown to be a potent inhibitor of hepcidin expression [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…TP-0184 is an ALK-2 inhibitor that reduces hepcidin mRNA and improves Hb concentration in preclinical studies in mice [14]. Modified heparin with reduced anticoagulation ability binds BMP-6 and blocks hepcidin expression, as demonstrated in in vitro and in vivo animal models [15,16].…”
Section: Drugs/substances Affecting Bmp6 Pathwaymentioning
confidence: 99%